Extraction camouflage treatment of a skeletal Class III malocclusion with severe anterior crowding by miniscrews and driftodontics in the mandibular dentition - Kai Zhang; Jiaojiao Li; Liyuan Yu; Wentian Sun; Kai Xia; Zhihe Zhao; Jun Liu (European Journal of Medical Research)
Abstract An 18-year-old Chinese woman presented with chief complaints of crowded teeth and mild mandibular prognathism. Clinical and imaging examinations revealed a concave profile, a protruded chin, increased lower anterior facial height mild, skeletal Class III and Angle’s Class III malocclusion, with anterior crossbites, and crowded teeth. Extraction camouflaged therapy combined with miniscrews skeletal anchorage was employed to relieve crowding and retract the mandibular anterior teeth. The total active treatment time was 31 months. After treatment, functional occlusion and smile esthetics were significantly improved.